Dynamics of torque teno virus load in kidney transplant recipients with indication biopsy and therapeutic modifications of immunosuppression - Reineke, Marvin; Morath, Christian; Speer, Claudius; Rudek, Markus; Bundschuh, Christian; Klein, Julian A.F.; Mahler, Christoph F.; Kälble, Florian; Nusshag, Christian; Beimler, Jörg; Zeier, Martin; Bartenschlager, Ralf; et al. (Frontiers in Medicine, 2024)
Following kidney transplantation, lifelong immunosuppressive therapy is essential to prevent graft rejection. On the downside, immunosuppression increases the risk for severe infections, a major cause of death among kidney transplant recipients (KTR). To improve post-transplant outcomes, adequate immunosuppressive therapy therefore is a challenging but vital aspect of clinical practice. Torque teno virus load (TTVL) was shown to reflect immune competence in KTR, with low TTVL linked to an elevated risk for rejections and high TTVL associated with infections in the first year post-transplantation. Yet, little is known about dynamics in TTVL after the first year following transplantation and how TTVL changes with respect to short-term modifications in immunosuppressive therapy. Therefore, we quantified TTVL in 106 KTR with 108 clinically indicated biopsies, including 65 biopsies performed >12 months post-transplantation, and correlated TTVL to histopathology. In addition, TTVL was quantified 7, 30 and 90 days post-biopsy to evaluate how TTVL was affected by changes in immunosuppression resulting from interventions based on histopathological reporting. TTVL was highest in patients biopsied between 1-12 months post- transplantation (N=23, median 2.98 × 10 7 c/mL) compared to those biopsied within 30 days (N=20, median 7.35 × 10 3 c/mL) and >1-year post-transplantation (N=65, median 1.41 × 10 4 c/mL; P<0.001 for both). Patients with BK virus-associated nephropathy (BKVAN) had significantly higher TTVL than patients with rejection (P<0.01) or other pathologies (P<0.001). When converted from mycophenolic acid to mTOR inhibitor following diagnosis of BKVAN, TTVL decreased significantly between biopsy to 30-and 90-days post-biopsy (P<0.01 for both). In KTR with highdose corticosteroid pulse therapy for rejection, TTVL increased significantly between biopsy to 30and 90-days post-biopsy (P<0.05 and P<0.01, respectively). Of note, no significant changes were seen in TTVL within 7 days of changes in immunosuppressive therapy. Additionally, TTVL varied considerably with time since transplantation and among individuals, with a significant influence of age and BMI on TTVL (P<0.05 for all). In conclusion, our findings indicate that TTVL reflects changes in immunosuppressive therapy, even in the later stages post-transplantation. To guide immunosuppressive therapy based on TTVL, one should consider inter-and intraindividual variations, as well as potential confounding factors.